2023
DOI: 10.3390/axioms12121083
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Neutrosophic Research: A Bibliometric Study

Camelia Delcea,
Adrian Domenteanu,
Corina Ioanăș
et al.

Abstract: In recent years, neutrosophic theory has garnered increasing attention within scholarly circles due to its applicability in various domains. Within these domains, the field of decision-making has derived significant advantages from the progressions in neutrosophic theory. Notably, neutrosophic theory has made substantial contributions by advancing and offering a range of aggregation operators and information measures specifically designed for enhancing decision-making processes. In this context, this study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…A total of 199 keywords have been documented, with an average of 3.55 keywords associated with each document. The obtained value is in line with other research from the field which has featured the use of a bibliometric analysis, being positioned at the superior limit of the expected data [52]. As the extracted papers on misinformation detection have been published mostly in the recent year, it has been observed that the issues related to keywords retrieval by WoS from the journals' websites or the situations in which the journals did not require for the papers to have keywords specified within their content-as discussed by Liu [56]-have been overcome.…”
Section: Dataset Overviewsupporting
confidence: 89%
See 1 more Smart Citation
“…A total of 199 keywords have been documented, with an average of 3.55 keywords associated with each document. The obtained value is in line with other research from the field which has featured the use of a bibliometric analysis, being positioned at the superior limit of the expected data [52]. As the extracted papers on misinformation detection have been published mostly in the recent year, it has been observed that the issues related to keywords retrieval by WoS from the journals' websites or the situations in which the journals did not require for the papers to have keywords specified within their content-as discussed by Liu [56]-have been overcome.…”
Section: Dataset Overviewsupporting
confidence: 89%
“…Biblioshiny provides insights about the analyzed area, along with highlighting crucial linkages between different aspects, considering its outstanding ability to evaluate data, design graphs, and create illustrations, interactive tables, and images [44]. Considering the scientific literature, it has been chosen for bibliometric analyses from various research areas, such as, but not being limited to: software testing [45], analyzing oil prices and financial assets [46], education [47], Industry 5.0 [48], the use of artificial intelligence in agent-based modeling [49], the use of agent-based modeling in transportation [50], grey systems theory [51], neutrosophic theory [52], and cybernetics [53].…”
Section: Part 2: Performing Bibilometric Analysismentioning
confidence: 99%
“…In terms of sources, the foremost position, according to the number of published papers, was occupied by IEEE Transactions on Industrial Informatics, with three articles. The journal belongs to the IEEE publishing house, internationally recognized in the academic community, as further evidenced by its rank among the top journals in other bibliometric studies conducted on different topics and published in the scientific literature [25,26,[28][29][30][80][81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…The interface is intuitive and easy to use, and it offers users the possibility to import data in row format in the frequently utilized R tool, Biblioshiny, which places Web of Science in the top of authors' preferences [25,26]. These aspects are further supported by the fact that many researchers who have conducted bibliometric studies have exclusively used the Web of Science database to extract the dataset (interested readers can refer to [25,[27][28][29][30][31]), to the detriment of other competitors, which once again underlines its prominent position within the scientific community.…”
Section: Dataset Extractionmentioning
confidence: 99%
“…The research methodology outlines the key stages involved in conducting the current study and elucidates the process for accessing the analyzed documents. The presentation of the information utilizes the Biblioshiny package [38], following a structure commonly employed in bibliometric analyses in various domains [39,40], including those focused on topics such as Industry 4.0 or Industry 5.0 [41,42].…”
Section: Methodsmentioning
confidence: 99%